A 13-Year-Old with Coexistence of Gastric Volvulus and Leprosy: A Case Report of Two Rare Entities - Joanna Schneider; Rhett Mays (Case Reports in Infectious Diseases)
Leprosy, or Hansen’s disease, is caused by infection with Mycobacterium leprae. It is a rare diagnosis within the continental United States. We present the case of a 13-year-old immigrant from the Marshall Islands who presented with recurrent nausea, vomiting, and abdominal pain which are found to be due to intermittent gastric volvulus. Gastric volvulus is also exceedingly rare, with less than 8 pediatric cases on average per year. During her second hospitalization for recurrent acute gastrointestinal issues, nonspecific skin lesions were biopsied, revealing infection with M. leprae. The patient did not exhibit classic symptoms of leprosy but did have prominent skin changes including diffuse nodules. This case explores the pathophysiology connecting leprosy to volvulus, discussing the possible role of an inflammatory response to infection in causing gastric volvulus. The finding of lepromatous leprosy may have been unrelated but was fortuitous, as early intervention will result in avoidance of debilitating peripheral neuropathy and eventual disfiguration from Hansen’s disease. This case highlights the importance of considering rare causes of gastric outlet obstruction including gastric volvulus and of considering leprosy in the differential for patients with unusual skin lesions or paresthesias who have a history of living or traveling in endemic areas.